Convention on Biological Diversity (CBD) and the Nagoya Protocol: Implications and Compliance Strategies for the Global Coffee Community - Dirk W. Lachenmeier; Christophe Montagnon (Foods, 2024)
The Nagoya Protocol on Access and Benefit-sharing (ABS) of the Convention on Biological Diversity (CBD) is a fundamental international agreement that plays a crucial role in the protection and equitable utilization of plant genetic resources. While this agreement is essential for conservation and sustainable use, it presents specific challenges to coffee research and industry. One major issue is the requirement to obtain prior informed consent (PIC) from the source country or community, which can be a complex and time-consuming process, especially in regions with limited governance capacity. Additionally, the mandates of this agreement necessitate benefit-sharing with the source community, a requirement that poses implementation challenges, particularly for small businesses or individual researchers. Despite these challenges, the importance of the Nagoya Protocol in the coffee sector cannot be overstated. It contributes significantly to the conservation of coffee genetic resources and the sustainable utilization of these resources, ensuring fair distribution of benefits. To address the complexities presented by this international framework, coffee researchers and industry need to engage proactively with source countries and communities. This includes developing clear and equitable benefit-sharing and implementing strategies for compliance. This article explores the impact of the Nagoya Protocol on the coffee industry, particularly emphasizing the need for balancing scientific investigation with the ethical considerations of resource sharing. It also discusses practical strategies for navigating the complexities of this agreement, including research focused on authenticity control and the challenges in conducting large-scale coffee studies. The conclusion underscores the potential for international collaboration, particularly through platforms like the International Coffee Organization (ICO), to harmonize research activities with the ethical imperatives of the Nagoya Protocol.